Social Norms for Behavior Change: A Synopsis - Laura A. Warner; Megan Cantrell; John M. Diaz (EDIS)
The purpose of this document is to discuss some of the important distinctions and definitions associated with social norms, so Extension professionals and other types of nonformal education practitioners can improve the efficacy of their behavior change interventions. This new 5-page publication of the UF/IFAS Department of Agricultural Education and Communication may be considered an advanced resource for those who are already familiar with basic principles of social norms. Written by Laura A. Warner, Megan S. Cantrell, and John M. Diaz. https://edis.ifas.ufl.edu/wc406